MENDORONG PERILAKU KERJA INOVATIF: PERAN KEPEMIMPINAN PATERNALISTIK DAN ORGANISASI PEMBELAJAR DALAM KONTEKS ORGANISASI PUBLIK - Almansyah Rundu Wonua; Niar Astaginy; Ismanto Ismanto (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
In the current era of global competition, organizations that want to continue to exist and develop must be able to produce innovative products or services. Innovative work behavior is one of the essential things that allows each individual or group to achieve organizational goals. This research was conducted to find out how the influence of paternalistic leadership and learning organizations on the innovative work behavior of PDAM Kolaka Regency employees. This study used a quantitative approach, with a data collection tool in the form of a questionnaire. The data collected was analyzed using structure equation modeling (SEM) with the help of the Smart PLS program. The results of the study show that there is no significant relationship between paternalistic leadership and innovative work behavior. This is due to wrong reasons. This is because in a paternalistic leadership style, leaders act like parents, so employees tend to rely on their leaders to provide direction and do not feel encouraged to take the initiative at work. While the influence of learning organization variables on innovative work behavior based on research results shows that it has an influence. This is because the training and employee development carried out by PDAM Kolaka Regency can be a means for employees to share experiences, knowledge, and innovative ideas, encouraging the exchange of ideas and better collaboration. Keywords: Paternalistic Leadership, Innovative Work Behavior